Pitfalls in Brain Death Diagnosis: A Case Report - Ruess, Daniel; Rieger, Bernhard; Goldbrunner, Roland; Schlacke, Hans-Peter (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Although there are distinct guidelines in nearly all countries, a reliable secure assessment of brain death in cases with open head injury can be challenging. We present a case of a 32-year-old man with severe head injury after intracranial penetration of a grindstone fragment. As the injury led to destruction of nearly the whole greater wing of the right sphenoid bone and parts of the right orbit, the examination of brainstem reflexes and the confirmation of brain death was unfeasible. On day 2, all clinical criteria of brain death (coma, absence of brainstem reflexes, apnea) were fulfilled. In addition, there was an extinction of brainstem auditory (BAEP) and cerebral (N20) components of median nerve somatosensory evoked potentials, while electroencephalogram (EEG) activity was still present. In the following days, a persisting EEG activity was obtained. Thus, an irreversible loss of whole brain functions could not be proved. As the patient had agreed to organ donation in case of brain death several years ago, ancillary methods to test the cessation of cerebral blood flow were mandatory. However, in this patient these methods turned out either to be doubtful or unavailable. For example, values of transcranial Doppler ultrasonography are not reliable in cases with open head injury. Due to a progressive septic state, time was running out to get the radiopharmaceutical agent for a cerebral scintigraphy (delivery time about 7 days, as the radiopharmaceutical agent was not in stock). Referring to the actual German guidelines, we had no legitimating indication for a cerebral angiography. Finally, the patient died of sepsis. We discuss the widening of the German guidelines in assessing brain death with the fast and low-risk method of cerebral computed tomography-angiography (CTA) to confirm diagnosis of brain death.
Keywords: brain death; brain injury; computed tomography (CT) angiography